Kiosk owners in Bihar help share videos on climate-smart agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
CCAFS together with ViDocs has produced ovcer 15 short films on climate-smart agriculture. They are useful extension matreial to scale out Climate-Smart Villages. But showcasing the films only through community screenings limits farmers' ability to access the videos when they want. Instead, we are working with village mobile phone kiosks to find out how they can share the videos directly with farmers. Find out more in this short film. Read more about our work (https://ccafs.cgiar.org/) Related blog on delivering agro advisories through mobile phones http://ow.ly/u31Qn